Management of Distal Radius Fractures in Adolescent Patients. (July 2021) - Greig, Danielle; Silva, Mauricio
Abstract : Background: While management recommendations for distal radius fractures in both young and skeletally mature patients have been generally well-established, controversy still exists regarding optimal management in adolescent patients approaching skeletal maturity. Thus, the goal of this review is to analyze relevant literature and provide expert recommendations regarding the management of distal radius fractures in this patient population. Methods: A PubMed search was performed to identify literature pertaining to distal radius fractures in adolescent patients, defined as 11 to 14 years in girls and 13 to 15 years in boys. Relevant articles were selected and summarized. Results: Distal radius fractures demonstrate significant potential for remodeling of angular deformity and bayonet apposition, even in patients older than 12 years of age. Rotational forearm range of motion and functional outcomes are acceptable with up to 15 degrees of residual angulation. Closed reduction and percutaneous pinning reduces fracture redisplacement but has a high associated complication rate. There is no literature comparing plate versus pin fixation of distal radius fractures in the pediatric population, but in adults plate fixation is associated with higher cost with no improvement in long-term functional outcomes. Conclusions: Remodeling can still be expected to occur in adolescent patients, and even with residual deformity functional outcomes after distal radius fractures are excellent. Up to 15 degrees of residual angulation can be accepted before considering operative management. Smooth pins should be considered over plates as first-line operative management for unstable fractures that fail nonoperative treatment.